Manfaat Sertifikat Produk Halal bagi pelaku Usaha Kecil dan Mikro di Lingkup Desa Nirannuang Kecamatan Bontomarannu - Astuti, Sry; Bahar, Hasrawati; Kining, Ekajayanti (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2024)
The aim of this service activity is to provide knowledge, understanding and assistance regarding the importance of halal certification for small and micro businesses in Nirannuang Village, Bontomarannu District, in order to provide insight and knowledge about the benefits of halal certified products. With this additional knowledge and understanding, it is hoped that it can increase productivity and competitiveness for small and micro businesses in Nirannuang Village, Bontomarannu District. Extension activities are carried out through the stage of socializing the benefits of halal product certification for small and micro business actors operating in the food sector. By providing information on the benefits of halal certification, the problem of the benefits of having a halal certificate for businesses, small and micro or UMKM that are considered useless can be resolved and become an example for other UMKM within the Nirannuang Village, Bontomarannu District. Purpose Legal counseling is held in an effort to provide knowledge and understanding of the importance of halal certification of a food product. The success of this outreach activity is supported by UMKM actors who are the target audience. Apart from this outreach activity, there is still a need for further action in the form of outreach on other legal materials that are useful for UMKM in Nirannuang Village, Bontomarannu District.